Therapeutic hypothermia initiated within 6 hours of birth is associated with reduced brain injury on MR biomarkers in mild hypoxic-ischaemic encephalopathy: a non-randomised cohort study. Issue 5 (13th November 2018) - Montaldo, Paolo; Lally, Peter J; Oliveira, Vânia; Swamy, Ravi; Mendoza, Josephine; Atreja, Gaurav; Kariholu, Ujwal; Shivamurthappa, Vijayakumar; Liow, Natasha; Teiserskas, Justinas; Pryce, Russell; Soe, Aung; et al.
Abstract : Objective: To examine the effect of therapeutic hypothermia on MR biomarkers and neurodevelopmental outcomes in babies with mild hypoxic-ischaemic encephalopathy (HIE). Design: Non-randomised cohort study. Setting: Eight tertiary neonatal units in the UK and the USA. Patients: 47 babies with mild HIE on NICHD neurological examination performed within 6 hours after birth. Interventions: Whole-body cooling for 72 hours (n=32) or usual care (n=15; of these 5 were cooled for <12 hours). Main outcome measures: MRI and MR spectroscopy (MRS) within 2 weeks after birth, and a neurodevelopmental outcome assessment at 2 years. Results: The baseline characteristics in both groups were similar except for lower 10 min Apgar scores (p=0.02) in the cooled babies. Despite this, the mean (SD) thalamic NAA/Cr (1.4 (0.1) vs 1.6 (0.2); p<0.001) and NAA/Cho (0.67 (0.08) vs 0.89 (0.11); p<0.001) ratios from MRS were significantly higher in the cooled group. Cooled babies had lower white matter injury scores than non-cooled babies (p=0.02). Four (27%) non-cooled babies with mild HIE developed seizures after 6 hours of age, while none of the cooled babies developed seizures (p=0.008). Neurodevelopmental outcomes at 2 years were available in 40 (85%) of the babies. Adverse outcomes were seen in 2 (14.3%) non-cooled babies, and none of the cooled babies (p=0.09). Conclusions: Therapeutic hypothermia may have a neuroprotective effect in babies with mild HIE, as demonstrated by improved MRS biomarkers and reduced white matter injury on MRI. This may warrant further evaluation in adequately powered randomised controlled trials.